KEKUATAN ALAT BUKTI REKAMAN SUARA DALAM PROSES PEMBUKTIAN TINDAK PIDANA KORUPSI DI INDONESIA - Putra, Rezki Dermawan; Artina, Dessy; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corruption is a problem for every country, therefore there is oneinstitution that has the authority to deal with and deal with this problem, inIndonesia this institution is called the Corruption Eradication Commission. TheCorruption Eradication Commission is an independent institution specifically setup to handle corruption cases that are equipped with a set of authorities incarrying out investigative, investigative and prosecuting duties, the KPK is giventhe authority to carry out interception or tapping and record conversations. Proofis the most important thing to look for justice. Basically, the law has been basedon it all, but the practice of proof in the field is not necessarily the reality thatshould be. In uncovering a corruption case in Indonesia, the use of sound proofevidence has been valid with the legal basis of Law Number 19 Year 2016concerning ITE, so that it can be known the importance of evidence evidence,especially voice recording evidence for disclosure of corruption cases in theRepublic of Indonesia in assisting the KPK in dealing with corruption cases.The purpose of this thesis is; first, to find out the strength of sound proofevidence in the process of proving corruption in Indonesia; second, to find out thelegal consequences of sound recordings obtained by illegitimate means in theprocess of proving corruption in Indonesia.In writing this thesis the author usesnormative research methods that emphasize the principles of law, namely theprinciple of legality, then analyzed qualitatively and make conclusions withdeductive methods.The research results of the author are; first, actually the institutionauthorized in wiretapping has been explained in the law is the KPK official legalbasis for Article 12 paragraph (1) Law 30 of 2002 concerning the CorruptionEradication Commission. KPK tapping at the investigation level is conducted tofind sufficient initial evidence to be able to proceed to the stage of investigationand legal subjects that can be subject to tapping are suspects in corruption.Second, proof is a form of seeking justice for every human being in the eyes of thelaw, proof is a way to convince a judge so that he can determine and realize thetruth in his verdict, using legal evidence that has been determined by law.Keywords: Eradication of Corruption-Proof-Ham Commission.